Green Supply Chain Learning And Green Innovation: The Moderating Role Of Market Turbulence (A Survey Of Firms In The Retail Sector In Greater Accra) - Duse, Barbarah (KNUST, 2023)
Green supply chain learning can lead to green innovation by providing companies with the knowledge and resources they need to develop new, more sustainable solutions. By working together, companies can create a more sustainable supply chain that benefits the environment and the bottom line. This thesis investigates the relationships between green supply chain learning and green innovation, considering the moderating role of market turbulence. The objectives of the study were to examine the moderating role of market turbulence on the relationship between supply chain learning and green innovation. A quantitative methodology was adopted, with survey data collected from 200 retail firms in Ghana. SMART-PLS was used to analyze the data. Structural equation modelling analysis showed green customer learning and significantly influence green innovation. Green supplier learning was also found to negatively impact green innovation. Moreover, market turbulence has a positive moderation effect on the relationship between green supply chain learning and green innovation. The study recommends managers revisit their supplier learning strategies with a critical eye. Instead of solely focusing on enhancing problem-solving capabilities, consider a more holistic approach. Also, Supply chain managers should recognize the immense value of well-informed and engaged customers in driving sustainable innovation efforts. Actively involve customers in the innovation process by seeking their feedback, preferences, and ideas. Moreover, Supply chain managers should acknowledge that market conditions can significantly impact the effectiveness of supplier-driven innovation. In turbulent markets, considering recalibrating innovation strategies is necessary.